â€œNational Festival Reyog Ponorogoâ€ As an Effort to Preserve Reyog Arts in Ponorogo Regency 1995-2016 - Fransisca Ayu Rismayanti; Marjono Marjono; Nurul Umamah (JURNAL HISTORICA, 2017)
National Festival Reyog Ponorogo is a staging of Reyog Arts with the format of the race held at the Main Stage of Ponorogo central park as one of the efforts made by the Government to preserve the Arts of Reyog Ponorogo. The art of Reyog, which was initially forgotten by many people ranging from young to old, increasingly decreasing demand by the current globalization. Reyog art cannot be used properly and experienced a shift. The younger generation is increasingly reluctant to preserve their ancestral cultures because they have thought that following the traditional arts it will be termed as non-modern young men. The purpose of this study is as one way to invite young people to participate preserve Reyog Arts to be known in various regions of the archipelago. This research is a historical research that has steps include: heuristics, criticism, interpretation and historiography. Data collection was done by observation, interview and documentation. The results of this research showed that the implementation of Reyog Ponorogo National Festival can preserve the Arts Reyog Ponorogo and promote the Ponorogo Regency as a tourist destination for local and foreign tourists. It is proven by the participation of festival participants from Sumatra, Kalimantan, DKI Jakarta, Yogyakarta, Universitas Brawijaya, Jember University, SMKN 2 Wonogiri etc. National Festival Reyog Ponorogo can increase the income of the people and the local government of Ponorogo through the trade, transportation and services sector as well as the hospitality sector. In addition, the festival can also be a medium for the planting of characters for the younger generation of the values pertained in the arts of Reyog Ponorogo. This research is expected to be a means to cultivate the interest of the young generation to preserve the arts of Reyog and can instil the values contained in Reyog Art so that the younger generation and society know that Reyog Art not only serves as a spectacle of neglect as well as life guidance. Keywords: National Festival Reyog Ponorogo, Conservation Efforts, Reog Arts Keywords: Reyog Ponorogo National Festival, Conservation Efforts, Reog Arts